Nitrogen-oxygen co-doped carbon felt electrode, preparation method and application thereof, and iron-chromium flow battery

CN122992092APending Publication Date: 2026-10-27SICHUAN UNIVERSITY OF SCIENCE AND ENGINEERING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611459368.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-20
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

(1)工艺创新:首次采用甲醇与N,N-二甲基甲酰胺的混合溶剂对碳毡进行一步溶剂热处理,利用DMF在加热条件下分解产生的含氮物种在碳毡表面原位引入氮官能团,同时甲醇分解产生的含氧物种协同引入含氧官能团(羟基、羰基、羧基),实现氮氧共掺杂改性。甲醇同时提供还原氛围,抑制碳骨架过度氧化。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992092A_ABST
    Figure CN122992092A_ABST
Patent Text Reader

Abstract

The application discloses nitrogen-oxygen co-doped carbon felt electrodes and a preparation method and application thereof and an iron-chromium flow battery, and relates to the technical field of electrochemical energy storage. The pretreated carbon felt is placed in a mixed solvent of methanol and DMF, and is subjected to solvothermal treatment at 120 DEG C to 160 DEG C for 12 h to 48 h, and then is carbonized at 600 DEG C to 800 DEG C for 0.5 h to 4 h in an inert atmosphere; wherein the volume ratio of methanol to DMF in the mixed solvent is (1.8-2.2):1; the electrode obtained by the method has rough carbon fiber surfaces and uniform nitrogen distribution, the Raman spectrum ID / IG value of the electrode is increased from 1.07 to 1.16, and the infrared spectrum has C-N and OH characteristic peaks, indicating that nitrogen and oxygen are successfully doped. LSV test shows that the hydrogen evolution side reaction is effectively inhibited, and the electrochemical reaction activity and reaction reversibility of the Cr3 + / Cr2 + redox couple are significantly improved, and the energy efficiency of the battery is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrochemical energy storage technology, specifically to nitrogen-oxygen co-doped carbon felt electrodes and their preparation methods and applications, and iron-chromium redox flow batteries. Background Technology

[0002] Iron-chromium redox flow batteries use inexpensive and abundant iron and chromium as active materials, and have significant cost advantages, high safety, long cycle life and environmental friendliness. They are regarded as one of the ideal technical routes in the field of large-scale energy storage, especially suitable for grid-connected power generation of renewable energy sources such as wind and solar power and grid peak shaving scenarios.

[0003] In an iron-chromium flow battery, Cr³⁺ is generated at the negative electrode. + / Cr² + Redox reaction. However, the intrinsic kinetics of this reaction are relatively slow, especially for Cr³⁺. + Reduced to Cr² + The process requires overcoming a high activation energy barrier, resulting in a large electrochemical overpotential. More importantly, within the negative electrode operating potential range, the hydrogen evolution side reaction (2H+) occurs... + +2e - →H2) has thermodynamic advantages and readily reacts with Cr³ + / Cr² + Reduction reactions create competition. The hydrogen evolution reaction not only directly reduces the coulombic efficiency of the battery, but also leads to increased H+ ionization in the electrolyte. + A decrease in chromium concentration and an increase in local pH can induce hydrolysis and precipitation of chromium (such as Cr(OH)3), further deteriorating electrode performance and affecting the long-term operational stability of the battery. Therefore, it is necessary to develop methods to control Cr³⁺ precipitation. + / Cr² + Anode materials with high catalytic activity and the ability to effectively suppress hydrogen evolution side reactions are a key technological bottleneck in improving the performance of iron-chromium redox flow batteries.

[0004] Carbon felt is widely used as an electrode material in iron-chromium flow batteries due to its three-dimensional network structure, high specific surface area, good electrical conductivity, and corrosion resistance. However, unmodified virgin polyacrylonitrile (PAN)-based carbon felt has insufficient reactive sites on its surface, which affects the reaction of Cr³⁺ with iron-chromium redox flow batteries. + / Cr² + The catalytic activity of the reaction is limited, and its selective inhibition of hydrogen evolution side reactions is poor. To improve the electrochemical performance of carbon felt, researchers have tried a variety of modification strategies, mainly including: acid / base treatment to introduce oxygen-containing functional groups, heat treatment to improve the degree of graphitization, metal catalyst loading, and heteroatom doping.

[0005] Nitrogen doping is considered a promising modification strategy. Both theoretical calculations and experimental studies show that introducing nitrogen atoms into the carbon framework alters the charge distribution of adjacent carbon atoms due to the high electronegativity of nitrogen, creating electron-rich regions. This enhances the adsorption capacity for chromium ions and reduces Cr³⁺. + / Cr² + The activation energy of the reaction.

[0006] Currently, common nitrogen doping methods mainly include: high-temperature heat treatment with ammonia (NH3), carbonization of nitrogen-containing precursors (such as melamine, urea, polyaniline, etc.), and plasma treatment. Among these, ammonia heat treatment is the most traditional method. However, this method usually requires high-temperature conditions above 700℃. Ammonia is highly corrosive and toxic, placing high demands on equipment and posing safety hazards. More importantly, while introducing nitrogen, high-temperature ammonia treatment often causes excessive etching of the carbon framework, generating numerous structural defects. Although a certain degree of defects can help increase active sites, excessive defects can lead to a decrease in the conductivity of carbon materials. More seriously, defect sites are often preferential active centers for hydrogen evolution reactions. Therefore, ammonia heat-treated modified carbon felts may actually exacerbate hydrogen evolution side reactions in actual operation, making it difficult to achieve an ideal balance between catalytic activity and hydrogen evolution inhibition.

[0007] Another common strategy is to co-blend nitrogen-containing small organic molecules (such as urea and melamine) with carbon felt precursors before carbonization. This method has poor controllability of nitrogen doping levels, and nitrogen-containing species are prone to agglomeration or removal during carbonization, making it difficult to achieve a uniform distribution of nitrogen on the carbon fiber surface. Furthermore, the high-temperature carbonization process also suffers from excessive carbon skeleton defects.

[0008] In summary, the existing nitrogen doping modification technologies generally have the following shortcomings: (1) high processing temperature and harsh process conditions, resulting in high energy consumption and cost; (2) nitrogen doping and structural defects are difficult to decouple, often resulting in "one thing at the expense of another" - while introducing nitrogen, excessive carbon defects are generated, which in turn aggravates the hydrogen evolution side reaction; (3) the uniformity of nitrogen distribution is difficult to guarantee, affecting the consistency of the overall electrode performance. Summary of the Invention

[0009] This invention addresses the shortcomings of existing technologies by providing a nitrogen-oxygen co-doped carbon felt electrode, its preparation method, and its application in iron-chromium redox flow batteries. The preparation method utilizes a mixed solvent of methanol and N,N-dimethylformamide to reduce and pre-dope the carbon felt surface with nitrogen at a relatively low temperature. Simultaneously, oxygen-containing species generated from methanol decomposition introduce oxygen-containing functional groups (hydroxyl, carboxyl, and carbonyl groups) onto the carbon felt surface, achieving nitrogen-oxygen synergistic doping modification. Combined with high-temperature carbonization to form a stable doped carbon framework, the process is mild and the doping is controllable, enabling the introduction of catalytically active sites while avoiding excessive destruction of the carbon framework, significantly improving the electrode's performance against Cr³⁺. + / Cr²+ The electrochemical reactivity and reversibility of the redox couple are enhanced, and the hydrogen evolution side reaction is effectively suppressed.

[0010] A first aspect of the present invention provides a method for preparing a nitrogen-oxygen co-doped carbon felt electrode, comprising the following steps: Solvent-thermal reduction-nitrogen-oxygen co-doping treatment: The pretreated carbon felt was immersed in a mixed solvent of methanol and N,N-dimethylformamide, transferred to a high-pressure reactor, and reacted at 120℃~160℃ for 12h~48h. After cooling, it was taken out, washed and vacuum dried to obtain the precursor carbon felt; wherein, the volume ratio of methanol to N,N-dimethylformamide in the mixed solvent was (1.8~2.2):1; High-temperature carbonization: The precursor carbon felt is heated to 600℃~800℃ under an inert atmosphere, held for 0.5h~4h, and then cooled to room temperature to obtain a nitrogen-oxygen co-doped carbon felt electrode.

[0011] Furthermore, the carbon felt is a polyacrylonitrile-based carbon felt with a thickness of 1 mm to 6 mm and a carbon mass fraction of 80% to 99%.

[0012] Furthermore, in the solvothermal reduction-nitrogen-oxygen co-doping treatment, the reaction temperature is 120℃~130℃, and the reaction time is 20h-30h.

[0013] Furthermore, in the high-temperature carbonization, the carbonization temperature is 600℃~650℃, and the holding time is 1.5h~2.5h.

[0014] Furthermore, in the high-temperature carbonization, the inert atmosphere is nitrogen or argon, and the gas flow rate is 50 mL / min to 200 mL / min; the heating rate is 3℃ / min to 20℃ / min.

[0015] Furthermore, before the solvothermal reduction-nitrogen-oxygen co-doping treatment, the carbon felt is pretreated, which includes: cutting the carbon felt into the required size, ultrasonically cleaning it sequentially with anhydrous ethanol and deionized water, and vacuum drying it.

[0016] In a second aspect, the present invention provides a nitrogen-oxygen co-doped carbon felt electrode prepared by the above-described preparation method.

[0017] Furthermore, the carbon framework of the nitrogen-oxygen co-doped carbon felt electrode is doped with nitrogen and oxygen elements, and the Raman spectrum ID / IG ratio of the nitrogen-oxygen co-doped carbon felt electrode is 1.10~1.20.

[0018] A third aspect of the present invention provides an application of the above-described nitrogen-oxygen co-doped carbon felt electrode in the negative electrode of an iron-chromium flow battery.

[0019] In a fourth aspect, the present invention provides an iron-chromium flow battery, wherein the negative electrode is the aforementioned nitrogen-oxygen co-doped carbon felt electrode.

[0020] Compared with the prior art, the present invention has at least the following beneficial effects: (1) Process innovation: For the first time, a mixed solvent of methanol and N,N-dimethylformamide was used to perform one-step solvothermal treatment on carbon felt. The nitrogen-containing species generated by the decomposition of DMF under heating conditions were used to introduce nitrogen functional groups in situ on the surface of carbon felt. At the same time, the oxygen-containing species generated by the decomposition of methanol were used to synergistically introduce oxygen-containing functional groups (hydroxyl, carbonyl, carboxyl), thus achieving nitrogen-oxygen co-doping modification. Methanol also provides a reducing atmosphere to inhibit the excessive oxidation of the carbon skeleton.

[0021] (2) Structural optimization: Compared with the original carbon felt, the ID / IG ratio of the obtained nitrogen-oxygen co-doped carbon felt is slightly increased (from about 1.07 to about 1.16), indicating that the moderate increase in defects provides more catalytic active sites; at the same time, the carbon fiber surface becomes rough (confirmed by SEM), which is beneficial to electrolyte wetting and ion mass transfer.

[0022] (3) Synergistic effect: Nitrogen doping sites (pyridine nitrogen, pyrrole nitrogen) effectively suppress hydrogen evolution side reaction (HER), and oxygen-containing functional groups (hydroxyl, carboxyl, carbonyl) significantly improve the hydrophilicity of carbon felt and electrolyte wettability, reducing interfacial mass transfer resistance; the synergistic effect of nitrogen and oxygen jointly promotes Cr³ + / Cr² + The reaction kinetics significantly improve battery energy efficiency. At a high current density of 160 mA / cm², the electrode of this invention still maintains an energy efficiency of 65.33%, while the original carbon felt electrode becomes ineffective.

[0023] (4) Mild conditions: The solvent heat treatment temperature is only 120℃~160℃, with low energy consumption and no need for external nitrogen source or reducing agent, making it green and environmentally friendly. Attached Figure Description

[0024] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments recorded in the embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings.

[0025] Figure 1 This is a comparison of the Raman spectra of the original carbon felt (CF) provided in Comparative Example 5 of the present invention and the nitrogen-oxygen co-doped carbon felt (CFRN) provided in Example 1.

[0026] Figure 2 The X-ray diffraction patterns are those of the original carbon felt (CF) provided in Comparative Example 5 and the nitrogen-oxygen co-doped carbon felt (CFRN) provided in Example 1.

[0027] Figure 3 The images show the SEM and EDS distributions of the original carbon felt (CF) provided in Comparative Example 5 and the nitrogen-oxygen co-doped carbon felt (CFRN) provided in Example 1 of this invention; wherein, (a) is the SEM image of CF; (b) is the SEM image of CFRN; (c) is the C element distribution in CF; (d) is the N element distribution in CF; (e) is the C element distribution in CFRN; and (f) is the N element distribution in CFRN.

[0028] Figure 4 The Fourier transform infrared (FTIR) spectrum of the original carbon felt (CF) provided as a comparative example of the present invention and the nitrogen-oxygen co-doped carbon felt (CFRN) provided in Example 1 is shown in the figure.

[0029] Figure 5 A comparison chart of linear sweep voltammetry (LSV) curves of the original carbon felt (CF) provided as a comparative example of the present invention and the nitrogen-oxygen co-doped carbon felt (CFRN) provided in Example 1.

[0030] Figure 6 The performance comparison of the original carbon felt (CF) provided as a comparative example of the present invention and the nitrogen-oxygen co-doped carbon felt (CFRN) provided in Example 1 in an iron-chromium flow battery is shown. Among them, (a) are the charge-discharge curves of CF and CFRN, ​​respectively; (b) are the energy efficiency curves of CF and CFRN as a function of current density, respectively; and (c) is a bar chart comparing the energy efficiency and coulombic efficiency of CF and CFRN at different current densities. Detailed Implementation

[0031] To better understand the above technical solutions, the technical solutions of the embodiments of this application will be described in detail below with reference to the accompanying drawings and specific embodiments. It should be understood that the embodiments of this application and the specific features in the embodiments are detailed descriptions of the technical solutions of the embodiments of this application, rather than limitations on the technical solutions of this application. In the absence of conflict, the embodiments of this application and the technical features in the embodiments can be combined with each other.

[0032] A first aspect of this invention provides a method for preparing a nitrogen-oxygen co-doped carbon felt electrode, comprising the following steps: Solvent-thermal reduction-nitrogen-oxygen co-doping treatment: The pretreated carbon felt was immersed in a mixed solvent of methanol and N,N-dimethylformamide, transferred to a high-pressure reactor, and reacted at 120℃~160℃ for 12h~48h. After cooling, it was taken out, washed and vacuum dried to obtain the precursor carbon felt; wherein, the volume ratio of methanol to N,N-dimethylformamide in the mixed solvent was (1.8~2.2):1; High-temperature carbonization: The precursor carbon felt is heated to 600℃~800℃ under an inert atmosphere, held for 0.5h~4h, and then cooled to room temperature to obtain a nitrogen-oxygen co-doped carbon felt electrode.

[0033] The preparation method of this invention is simple, low-cost, and easy to scale up, making it suitable for large-scale energy storage systems.

[0034] Specifically, this invention, for the first time, employs a methanol / N,N-dimethylformamide (DMF) mixed solvent for solvothermal treatment of carbon felt. The nitrogen-containing species generated by the decomposition of DMF under heating conditions introduce nitrogen functional groups in situ onto the carbon felt surface. Simultaneously, oxygen-containing species generated by the decomposition of methanol synergistically introduce oxygen-containing functional groups, achieving nitrogen-oxygen co-doping modification. Furthermore, methanol provides a reducing atmosphere, inhibiting excessive oxidation of the carbon skeleton. The entire solvothermal treatment process requires no external nitrogen source or reducing agent, making it environmentally friendly, and the temperature is only 120℃~160℃, significantly reducing energy consumption.

[0035] The selection of the solvothermal reaction temperature is based on the following: When the temperature exceeds 160℃, DMF undergoes violent decomposition, and the resulting highly reactive nitrogen atoms have sufficient energy to break through the carbon-based surface energy barrier, inserting extensively into six-membered carbon rings to form a graphitic nitrogen configuration. This directly exacerbates the hydrogen evolution side reaction, contradicting the original modification intention. Simultaneously, the rapid decomposition of methanol generates a large number of reducing free radicals that excessively etch the carbon fiber surface, producing numerous new active bare defects. This significantly increases the ID / IG ratio, damages the fiber structure, and significantly reduces mechanical strength, making it prone to breakage during long-term cycling. Furthermore, high temperatures cause thermal decomposition of oxygen-containing functional groups on the surface, worsening electrode hydrophilicity and electrolyte wettability, and increasing mass transfer resistance. Therefore, the reaction temperature must be controlled below 160℃.

[0036] 120℃ is the starting temperature range for the mild thermal decomposition of DMF. At this temperature, DMF can stably decompose to generate dimethylamine and nitrogen-containing active free radicals, achieving mild and controllable pre-nitrogen doping modification of carbon felt, effectively avoiding the unevenness caused by excessively rapid nitrogen doping at high temperatures. At the same time, methanol can play a moderate reducing role at 120℃, effectively inhibiting excessive oxidation on the carbon felt surface and ensuring the integrity and conductivity of the carbon skeleton. Therefore, the reaction temperature must not be lower than 120℃.

[0037] In summary, the mild range of 120℃ to 160℃ can ensure the controllable release of nitrogen-containing free radicals by DMF and the slow creation of a reducing atmosphere by methanol, while avoiding excessive etching of the carbon skeleton. This keeps ID / IG within a moderate range and prevents the generation of a large number of new hydrogen evolution active sites due to excessive reaction. It is a reasonable range that balances doping efficiency and structural integrity.

[0038] Regarding the control of solvothermal reaction time: a reaction time of 12h to 48h can ensure that hydroxyl groups and nitrogen-containing functional groups are uniformly grafted on the carbon fiber surface, resulting in a stable and consistent improvement in hydrophilicity. If the time is too short (below 12h), the doping reaction will be insufficient; if the time is too long (above 48h), it will cause excessive etching of the structure and a decrease in the mechanical properties of the fiber.

[0039] As a preferred option, in the solvothermal reduction-nitrogen-oxygen co-doping treatment, the reaction temperature is 120℃~130℃ and the reaction time is 20h~30h.

[0040] Regarding the ratio of the mixed solvent, the preferred volume ratio of methanol to DMF in this embodiment of the invention is 2:1. Experimental screening has shown that this ratio ensures sufficient nitrogen supply from DMF while utilizing the reducing properties of methanol to suppress excessive oxidation of the carbon skeleton, achieving an optimal balance between nitrogen doping amount and structural defect degree, thereby obtaining optimal electrochemical catalytic activity and hydrogen evolution inhibition capability.

[0041] The selection criteria for the high-temperature carbonization temperature are as follows: the carbonization temperature is controlled between 600℃ and 800℃. A carbonization temperature of 600℃ allows for the stable transformation of functional groups, fully converting the unstable nitrogen-containing functional groups introduced by solvothermal treatment into active nitrogen-doped structures, providing sufficient electrochemical active sites for the electrode. Simultaneously, a carbonization temperature not exceeding 800℃ avoids the problem of significant nitrogen removal under high-temperature conditions above 800℃, effectively preserving the active nitrogen components within the carbon framework and ensuring the performance stability of the modified electrode.

[0042] Preferably, the carbonization temperature is 600℃~650℃, and the holding time is 1.5h~2.5h. 600℃~650℃ falls within the medium-low temperature carbonization range, effectively removing unstable small molecules and oxygen-containing functional groups introduced by solvothermal processes. This temperature range allows for carbonization and shaping without damaging the nitrogen configuration constructed by solvothermal processes, while also requiring less equipment and consuming moderate energy. The 1.5h~2.5h holding time ensures uniform carbonization throughout the entire carbon felt, without performance gradient differences along the thickness direction.

[0043] In some embodiments, the carbon felt is a polyacrylonitrile-based carbon felt with a thickness of 1 mm to 6 mm and a carbon mass fraction of 80% to 99%.

[0044] Specifically, polyacrylonitrile (PAN)-based carbon felt has the following advantages: First, after carbonization, PAN forms a continuous sp² graphite carbon network, whose intrinsic conductivity is far superior to that of viscose-based carbon felt, which can significantly reduce ohmic polarization of the battery. Second, the three-dimensional interwoven fiber structure has interconnected pores, resulting in high electrolyte flow and ion mass transfer efficiency, making it suitable for high current density operating conditions. Third, the carbon skeleton after carbonization has strong chemical inertness, exhibiting excellent corrosion resistance in the strongly acidic electrolyte of iron-chromium batteries. It is not easily pulverized or broken during long-term cycling, and its cycle life is superior to that of pitch-based carbon felt. Fourth, the mass production technology of PAN precursor fibers is mature, and the finished carbon felt is inexpensive and has controllable specifications, meeting the grid energy storage demand for low-cost applications.

[0045] In some embodiments, during high-temperature carbonization, the inert atmosphere is nitrogen or argon, and the gas flow rate is 50 mL / min to 200 mL / min; preferably, the gas flow rate is 80 mL / min to 120 mL / min.

[0046] Specifically, a constant airflow can balance the temperature distribution inside the tubular furnace, ensuring uniform heating of the entire carbon felt. This eliminates the gradient difference between the front and rear ends in terms of carbonization degree and nitrogen doping ratio, significantly improving sample repeatability. Insufficient airflow can lead to localized gas accumulation and decreased atmosphere uniformity; excessive airflow, on the other hand, carries away a large amount of heat, lowering the actual furnace temperature and affecting the consistency of carbonization.

[0047] In some embodiments, during high-temperature carbonization, the heating rate is 3°C / min to 20°C / min; preferably, the heating rate is 8°C / min to 12°C / min.

[0048] Specifically, slow heating is key to ensuring a uniform reaction. Both the thermal oxidation and carbon skeleton rearrangement of carbon fibers are slow reaction processes. Low-speed heating allows heat to gradually penetrate into the fiber interior, ensuring that the etching and deoxidation reactions occur simultaneously on the surface and inside, avoiding structural differences caused by excessive ablation of the outer layer and insufficient modification of the interior due to rapid heating.

[0049] In some embodiments, the carbon felt is pretreated before the solvothermal reduction-nitrogen-oxygen co-doping treatment. The pretreatment includes cutting the carbon felt into the required size, ultrasonically cleaning it sequentially with anhydrous ethanol and deionized water, and vacuum drying it.

[0050] Specifically, the purpose of pretreatment is to remove surface impurities and residual moisture. Organic impurities such as spinning sizing agents, dust, and release agents remaining from the production process of commercial carbon felt can be thoroughly removed by ultrasonic cleaning, preventing the thermal decomposition of impurities during high-temperature heat treatment, which would generate amorphous carbon or impurity phases and interfere with nitrogen-oxygen co-doping and defect control. At the same time, removing residual moisture can prevent it from instantly vaporizing during the subsequent high-temperature activation / carbonization stage, avoiding irregular pores and localized over-etching on the fiber surface.

[0051] Optionally, the carbon felt pretreatment is as follows: the carbon felt is cut to the required size, ultrasonically cleaned 3 times with anhydrous ethanol for 10 minutes each time, then ultrasonically cleaned 3 times with deionized water for 10 minutes each time, and then vacuum dried at 80°C for 12 hours to obtain the original carbon felt (CF).

[0052] A second aspect of the present invention provides a nitrogen-oxygen co-doped carbon felt electrode prepared by the above-described preparation method.

[0053] Specifically, the nitrogen-oxygen co-doped carbon felt electrode incorporates nitrogen and oxygen elements in its carbon framework. The Raman spectral ID / IG ratio of the nitrogen-oxygen co-doped carbon felt electrode is 1.10–1.20, which is higher than that of the original carbon felt. This indicates that the solvothermal-pyrolysis treatment successfully introduced nitrogen doping and moderately increased the structural defects in the carbon framework, thus providing more electrochemical active sites. SEM confirmed that the carbon fiber surface has wrinkled textures and a nanoscale rough structure, which is beneficial for electrolyte wetting and ion mass transfer. The infrared spectrum shows the presence of CN and O. The H characteristic peak indicates successful nitrogen-oxygen doping.

[0054] A third aspect of the present invention provides the application of the above-described nitrogen-oxygen co-doped carbon felt electrode in the negative electrode of an iron-chromium flow battery.

[0055] A fourth aspect of the present invention provides an iron-chromium flow battery, wherein the negative electrode is the aforementioned nitrogen-oxygen co-doped carbon felt electrode. When used as the negative electrode of an iron-chromium flow battery, it significantly improves the Cr³⁺ content. + / Cr² + The electrochemical reactivity and reversibility of the redox couple are improved, the hydrogen evolution side reaction is effectively suppressed, and the battery energy efficiency is significantly improved.

[0056] Example 1: Preparation of nitrogen-oxygen co-doped carbon felt using methanol:DMF = 2:1 (volume ratio) (I) Preparation method Step (1): Pretreatment of carbon felt Commercially available polyacrylonitrile-based carbon felt (3.5 mm thick, carbon content 90%~95%, bulk density approximately 0.12 g / cm³) was cut into 3 cm × 3 cm square sheets. These sheets were then ultrasonically cleaned three times, for 10 minutes each time, with anhydrous ethanol (analytical grade, ≥99.7%) and deionized water (resistivity ≥18.2 MΩ·cm), at a frequency of 40 kHz and a power of 200 W. After cleaning, the sheets were stored at 80℃ and a vacuum degree ≤ The raw carbon felt was dried at 0.09 MPa for 12 h and labeled as CF.

[0057] Step (2): Solvothermal reduction Nitrogen doping treatment Add 40 mL of methanol and N,N to a 100 mL high-pressure reactor lined with polytetrafluoroethylene. 20 mL of dimethylformamide was used, with a volume ratio of 2:1. The pretreated CF was completely immersed in the above mixed solvent. After sealing the high-pressure reactor, the temperature was increased to 120 °C at a rate of 5 °C / min and maintained at this temperature for 24 h. After the reaction, the mixture was allowed to cool naturally to room temperature (cooling time was about 6 h). The carbon felt sample was then removed and washed three times alternately with deionized water and anhydrous ethanol. Subsequently, it was dried under vacuum at 80 °C for 12 h to obtain the nitrogen-doped pretreated precursor.

[0058] Step (3): High-temperature carbonization treatment The prepared precursor was placed horizontally in a corundum boat and placed in the isothermal region of a tubular furnace quartz tube. High-purity nitrogen gas (≥99.9% purity, gas flow rate 100 mL / min) was continuously introduced, and the furnace was purged for 30 min at room temperature to remove air. The temperature was then increased to 600℃ at a rate of 10℃ / min and held at this temperature for 2 h. After the holding period, the nitrogen gas flow was continuously introduced, and the furnace was allowed to cool naturally to room temperature, ultimately yielding nitrogen-oxygen co-doped carbon felt, labeled CFRN.

[0059] (ii) Battery performance testing The energy efficiency of the assembled iron-chromium redox flow battery was measured to be 82.56% under a current density of 80 mA / cm².

[0060] Comparative Example 1: Preparation of nitrogen-oxygen co-doped carbon felt using methanol:DMF = 1:1 (volume ratio) (I) Preparation method The difference from Example 1 is that step (2) is a solvothermal reduction. Nitrogen doping treatment: Add 30 mL of methanol and N,N to the high-pressure reactor. 30 mL of dimethylformamide was used, with the volume ratio of dimethylformamide to formaldehyde controlled at 1:1. All other operating procedures and parameters were identical to those in Example 1. The resulting nitrogen-oxygen co-doped carbon felt was labeled CFRN. 11.

[0061] (ii) Battery performance testing When assembling an iron-chromium redox flow battery, the energy efficiency of the battery corresponding to this electrode was measured to be 79.11% at a test current density of 80 mA / cm².

[0062] Comparative Example 2: Preparation of nitrogen-oxygen co-doped carbon felt using methanol:DMF = 3:1 (volume ratio) (I) Preparation method The difference from Example 1 is that step (2) is a solvothermal reduction. Nitrogen doping treatment: Add 45 mL of methanol and N,N to the high-pressure reactor. 15 mL of dimethylformamide was used, with the volume ratio of dimethylformamide to formamide controlled at 3:1. All other operating procedures and parameters were identical to those in Example 1. The resulting nitrogen-oxygen co-doped carbon felt was labeled CFRN. 31.

[0063] (ii) Battery performance testing The energy efficiency of the assembled iron-chromium redox flow battery was measured to be 78.06% under a current density of 80 mA / cm².

[0064] Comparative Example 3: Preparation of nitrogen-oxygen co-doped carbon felt using methanol:DMF = 4:1 (volume ratio) (I) Preparation method The difference from Example 1 is that step (2) is a solvothermal reduction. Nitrogen doping treatment: Add 48 mL of methanol and N,N to the high-pressure reactor. 12 mL of dimethylformamide was used, with the volume ratio of dimethylformamide to formaldehyde controlled at 4:1. All other operating procedures and parameters were identical to those in Example 1. The resulting nitrogen-oxygen co-doped carbon felt was labeled CFRN. 41.

[0065] (ii) Battery performance testing The energy efficiency of the assembled iron-chromium redox flow battery was measured to be 77.37% under a current density of 80 mA / cm².

[0066] Comparative Example 4: Preparation of nitrogen-oxygen co-doped carbon felt using only DMF (I) Preparation method The difference from Example 1 is that step (2) is a solvothermal reduction. Nitrogen doping treatment: Adding N,N to the high-pressure reactor 60 mL of dimethylformamide was used, and all other operating procedures and parameters were exactly the same as in Example 1. The resulting nitrogen-oxygen co-doped carbon felt was labeled CFRN. 01.

[0067] (ii) Battery performance testing The energy efficiency of the assembled iron-chromium redox flow battery was measured to be 75.98% under a current density of 80 mA / cm².

[0068] Comparative Example 5: Original carbon felt (CF) Preparation method The commercially available carbon felt was pretreated using only the process in step (1) of Example 1, without solvothermal reduction. Subsequent modification operations, such as nitrogen doping and high-temperature carbonization, yielded the original unmodified carbon felt, which served as the control sample CF.

[0069] Results Analysis (I) Performance comparison of different methanol to DMF volume ratios and determination of the optimal ratio Four different nitrogen-oxygen co-doped carbon felts prepared in Example 1 and Comparative Examples 1-4 were used as electrodes to assemble iron-chromium flow batteries. The core parameters of the batteries were uniformly set as follows: effective electrode area of ​​3 cm × 3 cm, and 1 mol / L Fe² electrolyte for both positive and negative electrodes. + / Fe³ + +1 mol / LCr³ + / Cr² + A mixed electrolyte of +3 mol / L HCl was used, and a Nafion 212 separator was selected. The battery charge / discharge cutoff voltage range was 0.7V~1.2V. Constant current charge / discharge tests were performed at a uniform current density of 80mA / cm². The energy efficiency test results of each sample battery are shown in Table 1.

[0070] Table 1 Energy efficiency of electrodes with different methanol / DMF volume ratios at 80 mA / cm²

[0071] As shown in Table 1, when the volume ratio of methanol to DMF is 2:1, the energy efficiency of the iron-chromium flow battery corresponding to the modified carbon felt electrode reaches the highest value of 82.56%, which is significantly better than other ratios. When the relative content of DMF is too high (methanol:DMF=1:1), excessive structural defects are generated in the carbon skeleton during the carbon felt modification process, resulting in a decrease in the overall conductivity of the electrode and a reduction in battery energy efficiency; the energy efficiency of the iron-chromium flow battery corresponding to the modified carbon felt electrode prepared with only DMF is 75.98%. When the proportion of methanol is too high (methanol:DMF=3:1, 4:1), the DMF as a nitrogen source in the system is relatively insufficient, the effective nitrogen doping amount on the carbon felt surface is greatly reduced, the doping modification effect is significantly weakened, and it is impossible to effectively improve the electrochemical performance of the electrode. In summary, this invention determines that methanol:DMF=2:1 (volume ratio) is the optimal modification ratio.

[0072] (II) Comparative analysis of nitrogen-oxygen co-doped carbon felt (CFRN) in Example 1 and original carbon felt (CF) in Comparative Example 5 The CFRN electrode prepared in Example 1 was used as the research object, and its microstructure was systematically characterized and its electrochemical performance was compared with that of the CF electrode in Comparative Example 5. All test equipment, test parameters and environmental conditions were kept consistent to ensure that the comparison results were accurate and reliable.

[0073] (1) Raman spectroscopy analysis The microstructure of CF and CFRN electrode samples was characterized using a Horiba LabRAM HR Evolution Raman spectrometer at an excitation wavelength of 532 nm. The test results are shown in [Figure number missing]. Figure 1 Test data shows that the ID / IG characteristic peak intensity ratio of the original CF was 1.072, while the ID / IG ratio of the modified CFRN sample increased to 1.159, an overall increase of approximately 8.1%. These test results demonstrate the solvothermal properties of this invention. The pyrolysis composite modification process can introduce a suitable amount of controllable structural defects into the carbon skeleton of the carbon felt. These defects can effectively expose more active sites at the electrode edges, further promoting the reaction between the carbon fibers and the electrolyte, and significantly improving the Cr³⁺ content. + / Cr² + The charge transfer efficiency during the redox reaction process was measured. Meanwhile, the ID / IG ratio of CFRN remained below 1.2, proving that the modification process did not severely damage the intrinsic graphite microcrystalline structure of the carbon felt, and the inherent conductivity of the electrode was effectively preserved, achieving a balance between defect activity and conductivity.

[0074] (2) X-ray diffraction (XRD) analysis The crystal structure of the two groups of samples was characterized using X-ray diffraction (CuKα radiation, wavelength λ = 0.15406 nm, scanning angle range 10°~90°). The test results are shown in [Figure number missing]. Figure 2 The CF sample exhibits a typical (002) diffraction peak characteristic of hexagonal graphite structure near 26.6°. Compared to the CF sample, the (002) characteristic diffraction peak of the CFRN sample shifts slightly to a higher angle, and the half-width at half-maximum (WHM) of the diffraction peak is slightly narrower. This phenomenon indicates that high-temperature carbonization treatment can optimize the microcrystalline structure of carbon felt graphite, increase the size of graphite crystallites, reduce the carbon interlayer spacing, effectively improve the orderliness of the carbon skeleton structure, and thus improve the intrinsic conductivity of carbon fibers and reduce the electrode charge transport resistance.

[0075] (3) Scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) analysis The microstructure of CF and CFRN was observed using field emission scanning electron microscopy, and elemental distribution analysis was performed using EDS elemental surface scanning. The test results are shown in [Figure number missing]. Figure 3 . Figure 3 In sample (a) of CF, the carbon fiber surface is flat and smooth, and the microscopic specific surface area is small; Figure 3 (b) via solvothermal After high-temperature carbonization modification, the CFRN sample exhibits a large number of nanoscale wrinkles and pitted rough structures on the carbon fiber surface, which significantly increases the electrode specific surface area and provides a sufficient active interface for electrolyte wetting, ion adsorption and mass transfer. Figure 3 (c)~ Figure 3The EDS elemental distribution test results in (f) confirm that nitrogen is uniformly distributed on the surface of the CFRN sample in the overall carbon fiber structure, which fully proves that the process of the present invention has successfully achieved uniform nitrogen doping modification.

[0076] (4) Fourier transform infrared spectroscopy (FTIR) analysis To demonstrate the successful incorporation of nitrogen into the carbon framework, infrared spectroscopy (wavenumber range 4000 cm⁻¹) was performed on the CFRN carbon felt. - ¹~500cm - ¹), the results are as follows Figure 4 As shown in Table 2, the key absorption peaks are assigned to key absorption peaks.

[0077] Table 2. Assignment and significance of key absorption peaks in Fourier transform infrared spectra

[0078] The infrared spectrum of the original CF sample did not show a value of 1540 cm⁻¹. - ¹ Characteristic absorption peaks near 1540 cm⁻¹; while CFRN samples show characteristic absorption peaks at 1540 cm⁻¹. - ¹A significant C appears at the wavenumber. The characteristic shoulder peak of the N covalent stretching vibration directly proves that nitrogen is stably incorporated into the carbon felt carbon framework in the form of covalent bonds, completing effective nitrogen doping. Meanwhile, the CFRN sample at 3430 cm⁻¹... - ¹O The significantly enhanced intensity of the characteristic peak of the H functional group indicates that the solvothermal modification process can synergistically introduce a large number of oxygen-containing hydrophilic functional groups, effectively enhancing the hydrophilicity of the electrode surface and further optimizing the electrolyte wetting effect.

[0079] The improvement of electrode performance by oxygen-containing functional groups is mainly reflected in the following three aspects: Firstly, it enhances hydrophilicity. The hydroxyl and carboxyl groups are polar groups, which can significantly reduce the contact angle between the carbon felt surface and the aqueous electrolyte, making it easier for the electrolyte to penetrate into the three-dimensional network structure inside the carbon felt, shortening the ion transport path, and reducing concentration polarization.

[0080] Secondly, they provide auxiliary active sites. Oxygen-containing functional groups such as carboxyl and carbonyl groups are associated with Cr³⁺. + It has preferential adsorption capacity and can form a synergistic functional zone of "liquid-adsorption-catalysis" with nitrogen doping sites, further reducing interfacial mass transfer resistance.

[0081] Third, it improves electrode stability. The oxygen-containing functional groups are covalently bonded to the carbon skeleton, making them less prone to desorption during long-term battery cycling, thus ensuring the long-term stability of electrode performance.

[0082] In summary, the introduction of oxygen-containing functional groups is not an isolated surface modification, but rather works synergistically with nitrogen doping to jointly promote the overall improvement of the anode performance of iron-chromium flow batteries.

[0083] (5) Linear sweep voltammetry (LSV) test A standard three-electrode testing system (working electrode: CF or CFRN, ​​effective area 1 cm²; saturated calomel electrode as reference electrode; platinum sheet as counter electrode) was used. The negative electrode polarization curve of the sample was measured in a 3 mol / L HCl electrolyte system at a scan rate of 5 mV / s. The test results are shown in [Figure number missing]. Figure 5 Test data shows that for CF and CFRN, ​​the potentials required to drive a 100mA current are respectively... 17.81mV and 23.23 mV. It is evident that the HER overpotential of CFRN is significantly greater than that of CF. The significant increase in CFRN's hydrogen evolution overpotential is attributed to the introduction of nitrogen-doped functional groups, which effectively raises the reaction barrier of the hydrogen evolution side reaction and suppresses competing hydrogen evolution side reactions during the operation of the iron-chromium flow battery. In summary, CFRN can effectively suppress hydrogen evolution side reactions and significantly improve the Cr³⁺ overpotential. + / Cr² + Electrochemical reactivity and reversibility of redox couples.

[0084] (6) Performance comparison of iron-chromium redox flow batteries Single cells were assembled using CF and CFRN as the negative electrodes, respectively, with the same assembly parameters as described above. Constant current charge-discharge tests were conducted at gradient current densities of 80 mA / cm², 100 mA / cm², 120 mA / cm², 140 mA / cm², and 160 mA / cm². Detailed performance data are shown in Table 3, and the battery charge-discharge curves are shown in [reference needed]. Figure 6 In section (a), the energy efficiency versus current density curve is shown in Figure 1. Figure 6 (b) See the bar chart comparing coulombic efficiency and energy efficiency. Figure 6 (c)

[0085] Table 3 Battery performance of CF and CFRN at different current densities

[0086] Combining the data in Table 3 with Figure 6Test results show that, compared to the original CF electrode, the battery assembled with the CFRN electrode exhibits a lower charging plateau potential and a higher discharging plateau potential at various current densities, with a significant reduction in battery polarization overpotential. The three core performance indicators—coulombic efficiency (CE), voltage efficiency (VE), and energy efficiency (EE)—are all superior to those of the original CF electrode. Crucially, even at a high current density of 160 mA / cm², the CFRN electrode can still stably complete charge-discharge cycles, maintaining an energy efficiency of 65.33%, while the original CF electrode cannot achieve normal charge-discharge operation. These test results fully demonstrate that the CFRN-modified electrode prepared in this invention possesses excellent rate performance and hydrogen evolution side reaction suppression capabilities, significantly improving the overall performance and operating condition adaptability of iron-chromium redox flow batteries.

[0087] It will be readily understood by those skilled in the art that the above-described advantageous methods can be freely combined and superimposed without conflict. The above are merely preferred embodiments of this application and are not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application. The above are merely preferred embodiments of this application. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the technical principles of this application, and these improvements and modifications should also be considered within the protection scope of this application.

Claims

1. A method for preparing a nitrogen-oxygen co-doped carbon felt electrode, characterized in that, Includes the following steps: Solvent-thermal reduction-nitrogen-oxygen co-doping treatment: The pretreated carbon felt was immersed in a mixed solvent of methanol and N,N-dimethylformamide, transferred to a high-pressure reactor, and reacted at 120℃~160℃ for 12h~48h. After cooling, it was taken out, washed and vacuum dried to obtain the precursor carbon felt; wherein, the volume ratio of methanol to N,N-dimethylformamide in the mixed solvent was (1.8~2.2):1; High-temperature carbonization: The precursor carbon felt is heated to 600℃~800℃ under an inert atmosphere, held for 0.5h~4h, and then cooled to room temperature to obtain a nitrogen-oxygen co-doped carbon felt electrode.

2. The preparation method according to claim 1, characterized in that, The carbon felt is a polyacrylonitrile-based carbon felt with a thickness of 1 mm to 6 mm and a carbon mass fraction of 80% to 99%.

3. The preparation method according to claim 1, characterized in that, In the solvothermal reduction-nitrogen-oxygen co-doping treatment, the reaction temperature is 120℃~130℃ and the reaction time is 20h-30h.

4. The preparation method according to claim 1, characterized in that, In the high-temperature carbonization, the carbonization temperature is 600℃~650℃, and the holding time is 1.5h~2.5h.

5. The preparation method according to claim 1, characterized in that, In the high-temperature carbonization process, the inert atmosphere is nitrogen or argon, and the gas flow rate is 50 mL / min to 200 mL / min; the heating rate is 3℃ / min to 20℃ / min.

6. The preparation method according to claim 1, characterized in that, Before the solvothermal reduction-nitrogen-oxygen co-doping treatment, the carbon felt is pretreated. The pretreatment includes: cutting the carbon felt into the required size, ultrasonically cleaning it with anhydrous ethanol and deionized water in sequence, and vacuum drying it.

7. A nitrogen-oxygen co-doped carbon felt electrode prepared by the preparation method according to any one of claims 1-6.

8. The nitrogen-oxygen co-doped carbon felt electrode according to claim 7, characterized in that, The nitrogen-oxygen co-doped carbon felt electrode has nitrogen and oxygen elements doped in its carbon framework, and the Raman spectrum ID / IG ratio of the nitrogen-oxygen co-doped carbon felt electrode is 1.10~1.

20.

9. The application of the nitrogen-oxygen co-doped carbon felt electrode as described in claim 7 or 8 in the negative electrode of an iron-chromium flow battery.

10. An iron-chromium redox flow battery, characterized in that, Its negative electrode is the nitrogen-oxygen co-doped carbon felt electrode as described in claim 7 or 8.